PENYULUHAN HUKUM: PENGABDIAN KEPADA MASYARAKAT DALAM KESADARAN HUKUM SISWA SMA NEGERI 1 BALEENDAH TENTANG AKIBAT HUKUM JUDI ONLINE - Widjanarto, Haswar; Nitipradja, Aldy Subianto (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
The escalation of the online gambling phenomenon among students, accelerated by advances in information technology, underscores the urgency of this research. This study focuses on assessing students' level of legal awareness regarding the legal consequences of online gambling, from a criminal, civil, and administrative perspective. Conducted through interactive legal counseling on May 14, 2025, with 30 students, the methods employed included case studies, focused discussions, and critical thinking. The research findings demonstrate a significant increase in respondents' understanding of the legal implications. Online gambling clearly violates Article 303 of the Criminal Code and the Electronic Information and Transactions Law, while also triggering potential civil disputes and administrative sanctions in the form of access blocking and financial transaction monitoring. In addition to legal risks, destructive socio-economic impacts were also identified, including financial loss to families, increased crime, and mental health disorders. The main conclusion emphasizes that efforts to eradicate online gambling require a multidisciplinary approach that relies not only on law enforcement but also on the integration of digital literacy and synergistic collaboration between the government, schools, and the community to protect the younger generation from moral and legal degradation. ABSTRAKEskalasi fenomena judi online di kalangan pelajar yang terakselerasi oleh kemajuan teknologi informasi menjadi latar belakang urgensi penelitian ini. Studi ini berfokus pada penilaian tingkat kesadaran hukum siswa terhadap konsekuensi yuridis perjudian daring, baik dari perspektif pidana, perdata, maupun administratif. Dilaksanakan melalui penyuluhan hukum interaktif pada 14 Mei 2025 terhadap 30 siswa, metode yang diterapkan meliputi studi kasus, diskusi terarah, dan berpikir kritis. Temuan penelitian menunjukkan peningkatan signifikan pada pemahaman responden mengenai implikasi hukum, di mana judi online secara tegas melanggar Pasal 303 KUHP serta UU ITE, sekaligus memicu potensi sengketa perdata dan sanksi administratif berupa pemblokiran akses serta pengawasan transaksi keuangan. Selain risiko hukum, teridentifikasi pula dampak destruktif pada aspek sosial-ekonomi, termasuk kerugian finansial keluarga, peningkatan kriminalitas, hingga gangguan kesehatan mental. Simpulan utama menegaskan bahwa upaya pemberantasan judi online memerlukan pendekatan multidisipliner yang tidak hanya mengandalkan penegakan hukum, tetapi juga integrasi literasi digital dan kolaborasi sinergis antara pemerintah, sekolah, dan masyarakat untuk memproteksi generasi muda dari degradasi moral dan hukum.